Tecnologia para assistência de enfermagem às pacientes internadas em uma Unidade de Trapia Intensiva materna - Sá, Fabíola Nunes de (2020)
The objective was to validate a technology for nursing care for patients admitted to a Maternal Intensive Care Unit. To this end, a methodological study was carried out in four stages: 1) Integrative review of the literature on the Nursing process for women in the puerperal pregnancy cycle in a maternal ICU; 2) Construction of the Nursing history directed to obstetric patients in intensive care; 3) Adaptation of Gomes' instrument (2016) for use in the maternal ICU, based on the results of the integrative review; 4) Validation of the instrument's appearance and content by expert judges. The integrative review followed the steps proposed by Whittemore and Knafl (2005). The literary search was carried out in pairs with double-blind methodology, in the databases: LILACS, CINAHL and Scopus, using the controlled descriptors: pregnant women, pregnancy, nursing process, nursing diagnosis, standardized nursing terminology, intensive care units; and MEDLINE with the descriptors: pregnant women, pregnant woman, parturient, puerperal, nursing process, nursing care, nursing care management, patient care planning, nursing diagnosis, nursing interventions classification, intensive care units. In the second stage, the nursing history of the service was edited and updated, in order to structure the data collection based on the basic human needs contained in the proposed theoretical model of Wanda Horta (2018), according to the psychobiological, psychosocial and psycho-spiritual dimensions. In the third stage, a parallel was made between Gomes' instrument (2016) and the result of the integrative literature review, to identify the items of the Nursing process present in the review that complement the instrument, for the execution of the version of the technology to be validated by the experts. In the fourth stage, appearance and content validation was performed by expert judges in the Nursing Process. The study respected the ethical aspects of research involving human beings as determined by Resolution No. 466 of December 12, 2012, and was approved by the MEAC Research Ethics Committee (CEP), under number 4,145,669. Changes were made to the Nursing History, which included three sections: I. Identification; II. Basic human needs; III. Physical exam; and IV. Basic human needs assessment. The Nursing Care Plan for High-Risk Pregnant Women was restructured with 34 diagnoses, organized into basic human needs (psychobiological, psychosocial and psycho-spiritual). The last stage of validation by the judges occurred in a total period of 30 days and completely online, with the participation of 22 judges, a satisfactory level of validation of the appearance of the data collection instrument was obtained (IVC: 92.1) and assistance technology (91.3%). In the content validation, similarly to the appearance, the data collection instrument and the assistive technology were validated, with 100% of the tables reaching a satisfactory level and with CVI 88.5 and 82.4, respectively. Thus, at the end, 34 nursing diagnoses and their nursing interventions and actions were consolidated. Through this study it was possible to develop a technological instrument for nursing care to patients admitted to a Maternal Intensive Care Unit based on basic human needs.